The Double-Edged Sword of Oxidative Stress in Skin Damage and Melanoma: From Physiopathology to Therapeutical Approaches - Monica Emanuelli (Antioxidants, 2022)
The skin is constantly exposed to exogenous and endogenous sources of reactive oxygen species (ROS). An adequate balance between ROS levels and antioxidant defenses is necessary for the optimal cell and tissue functions, especially for the skin, since it must face additional ROS sources that do not affect other tissues, including UV radiation. Melanocytes are more exposed to oxidative stress than other cells, also due to the melanin production process, which itself contributes to generating ROS. There is an increasing amount of evidence that oxidative stress may play a role in many skin diseases, including melanoma, being the primary cause or being a cofactor that aggravates the primary condition. Indeed, oxidative stress is emerging as another major force involved in all the phases of melanoma development, not only in the arising of the malignancy but also in the progression toward the metastatic phenotype. Furthermore, oxidative stress seems to play a role also in chemoresistance and thus has become a target for therapy. In this review, we discuss the existing knowledge on oxidative stress in the skin, examining sources and defenses, giving particular consideration to melanocytes. Therefore, we focus on the significance of oxidative stress in melanoma, thus analyzing the possibility to exploit the induction of oxidative stress as a therapeutic strategy to improve the effectiveness of therapeutic management of melanoma.